The influence of the time of single photon transmission of information on the reliability of its reception in a quantum cryptographic communication channel - A. M. Timofeev (Системный анализ и прикладная информатика)
Expression for estimating the reliability of information during its transmission through quantum-cryptographic communication channel that contains a dead time photon counter has been obtained in this research. According to the results of mathematical modeling, the dependence of the reliability of the received data on the average time of single photon transmission of information was established. Studies have shown that with an increase in the average time of single photon transmission of information, these dependences grow, reaching saturation. Moreover, with equal parameters with an increase in the average duration of the dead time of a prolonging type, saturation occurs at large values of the average time of a single photon transmission of information.